The Google reader (Prassi Ecdotiche della Modernità Letteraria, 2016)
Publishers of 21st Century have to face a new problem: the digital revolution. They have to deal with new reading habits and with new publishing habits. The so-called “Google-readers” often search for books on the web, but those texts sometimes are not “certified” by a publisher. There are some standards that on-line books should observe: declaring who is the editor of that edition, declaring which text is published (and which paper edition the editor has used), declaring which are the metadata connected with that edition, making that edition user friendly. None of the Italian websites fully satisfies those standards and is well indexed by browsers. WIKI-source is one of the best websites, but it does not make use of scholarly editions and it does not spread the most authoritative edition, but the one available to the web editor. The edition of I Promessi Sposi, for example, is not based on a scholarly edition, but on the most recent paper editions, and readers still have to consult them if they want to get further informations.
Keywords: google; readers; WIKI-source; digital editions; web texts; Manzoni